Error-Related Dynamics of Reaction Time and Frontal Midline Theta Activity in Attention Deficit Hyperactivity Disorder (ADHD) During a Subliminal Motor Priming Task - Keute, Marius; Stenner, Max-Philipp; Mueller, Marie-Kristin; Zaehle, Tino; Krauel, Kerstin (Frontiers in Human Neuroscience, 2019)
Post-error slowing (PES) is an established performance monitoring readout. Several previous studies have found that PES is reduced in children and adolescents with attention-deficit hyperactivity disorder (ADHD). We analyzed reaction time data, along with EEG data, from a response priming experiment in children and adolescents with ADHD (N = 28) and typically developing (TD) controls (N = 15) between 10 and 17 years of age. We report dynamic reaction time changes before and after errors: Whereas TD controls readjusted their response speed to their individual average speed after committing an error, this reaction time adjustment appeared to be delayed and decreased in ADHD patients. In the EEG, error trials were accompanied by increased frontal midline theta activity, which was attenuated in ADHD compared to TD. We conclude that PES has a different time course rather than being fully absent in ADHD and discuss relationships to our EEG findings and potential implications for performance monitoring in ADHD.